Features of Structural Hardware Transformation of Information in Cryptosystems - A. F. Chernyavskiy; E. I. Kozlova; Yu. A. Chernyavskiy (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The article considers types, functions and some features of cryptosystems, as well as circuit design options for expanding their functionality. Options for generating keys and ciphers used in cryptosystems with a typical structural organization, and technologies for creating encryption chains are presented. An encryption scheme is described, in the recurrent formula of the algorithm of which the previous blocks of both encryption and plaintext are used. This scheme reliably protects against any unauthorized modiﬁcation of the encrypted text. Structural diagrams of the organization of symmetric and asymmetric cryptosystems are given. A variant of implementing a decoding procedure in a threshold MIMA cryptomodule for sharing a secret with a masking transformation is proposed, in which the necessary time and hardware costs for performing the procedure of reconstructing the original secret are minimized. The presented material can be the part of the original sections of a necessary and suﬃciently provided in mathematical terms textbook on the basics and modern problems of cryptography.